Using bacteriophages against Paenibacillus larvae for the prevention and treatment of American Foulbrood disease in honeybee colonies - Alippi, Adriana Mónica (2019)
American Foulbrood (AFB) of honey bees is the most contagious and destructive infectious disease affecting the larval and pupal stages of honey bees (Apis mellifera) and other Apis species. The causative agent, Paenibacillus larvae, is a Gram-positive bacterium that can produce over one billion spores in each infected larva. AFB occurs throughout the world and leads to considerable losses in apiculture and pollination. The disease is classified within the World Organization for Animal Health (OIE) list and considered to be of socio-economic impact and significance in the international trade of bees and bee products. Only bacterial spores are capable of inducing the infection. Spores can remain viable in comb and woodenware for decades and survive adverse conditions (desiccation, high temperatures, ultraviolet light exposure) and contact with standard disinfectants. The spread of the disease is facilitated by regular beekeeping practices, including exchanging hive components between colonies, maintaining many hives in a confined area, and trading queens, package bees and honey.